Vertical Accuracy Assessment of ALOS PALSAR, GMTED2010, SRTM and Topodata Digital Elevation Models - Ferreira, Zuleide A. (2021)
Ferreira, Z. A., & Cabral, P. (2021). Vertical Accuracy Assessment of ALOS PALSAR, GMTED2010, SRTM and Topodata Digital Elevation Models. In Proceedings of the 7th International Conference on Geographical Information Systems Theory, Applications and Management (GISTAM 2021) (pp. 116-124). SCITEPRESS - Science and Technology Publications, Lda. https://doi.org/10.5220/0010404001160124